Redox Regulation of Cardiac ASK1 (Apoptosis Signal-Regulating Kinase 1) Controls p38-MAPK (Mitogen-Activated Protein Kinase) and Orchestrates Cardiac Remodeling to Hypertension - Meijles, Daniel N. (Hypertension, 2020)
Systemic hypertension increases cardiac workload causing cardiomyocyte hypertrophy and increased cardiac fibrosis. An underlying feature is increased production of reactive oxygen species. Redox-sensitive ASK1 (apoptosis signal-regulating kinase 1) activates stress-regulated protein kinases (p38-MAPK [mitogen-activated protein kinases] and JNKs [c-Jun N-terminal kinases]) and promotes fibrosis in various tissues. Here, we determined the specificity of ASK1 signaling in the heart, with the hypothesis that ASK1 inhibitors may be used to manage fibrosis in hypertensive heart disease. Using immunoblotting, we established that moderate levels of H(2)O(2) activate ASK1 in neonatal rat cardiomyocytes and perfused rat hearts. ASK1 was activated during ischemia in adult rat hearts, but not on reperfusion, consistent with activation by moderate (not high) reactive oxygen species levels. In contrast, IL (interleukin)-1β activated an alternative kinase, TAK1 (transforming growth factor–activated kinase 1). ASK1 was not activated by IL1β in cardiomyocytes and activation in perfused hearts was due to increased reactive oxygen species. Selonsertib (ASK1 inhibitor) prevented activation of p38-MAPKs (but not JNKs) by oxidative stresses in cultured cardiomyocytes and perfused hearts. In vivo (C57Bl/6J mice with osmotic minipumps for drug delivery), selonsertib (4 mg/[kg·d]) alone did not affect cardiac function/dimensions (assessed by echocardiography). However, it suppressed hypertension-induced cardiac hypertrophy resulting from angiotensin II (0.8 mg/[kg·d], 7d), with inhibition of Nppa/Nppb mRNA upregulation, reduced cardiomyocyte hypertrophy and, notably, significant reductions in interstitial and perivascular fibrosis. Our data identify a specific reactive oxygen species→ASK1→p38-MAPK pathway in the heart and establish that ASK1 inhibitors protect the heart from hypertension-induced cardiac remodeling. Thus, targeting the ASK1→p38-MAPK nexus has potential therapeutic viability as a treatment for hypertensive heart disease.